(untitled) (Indonesian Art and Justice Review, 2025)
In Indonesia, the tension between artistic freedom and censorship remains a critical issue, particularly as political and religious authorities exercise control over the content of public and private art. This paper explores the boundaries of creative expression in Indonesia, focusing on how censorship—both institutional and societal—limits artists’ ability to critique the state, challenge dominant ideologies, or address sensitive political issues. By examining case studies of banned artworks, protests against governmental policies, and the role of censorship laws, the study highlights the ways in which art navigates, resists, and sometimes succumbs to political and religious pressures. The paper argues that censorship is not just a tool of repression but also a catalyst for artistic innovation, forcing artists to find creative ways to communicate their messages while negotiating the legal and moral limits of expression in Indonesia.